Pemanfaatan BIM dalam Integrasi Arsitektur dan MEP Pada Proyek Konstruksi Gedung Lab PUT PNJ - Seftiani, Nadia; Widiasanti, Irika; Wangi, Intan Puspa (Universitas Batanghari Jambi, 2024)
Recent building construction projects increasingly prioritize the integration of architectural (design) and MEP (mechanical, electrical, and plumbing) aspects as key elements to achieve effective and sustainable projects. This study aims to explore the close relationship between architecture and MEP in building construction projects and how integrating the two can provide optimal results. This article discusses the important role of Building Information Modeling (BIM) technology in supporting the integration of architecture and MEP. BIM enables architecture and MEP professionals to work collaboratively in an integrated virtual environment, facilitating monitoring, coordination, and early identification of design conflicts. The results showed that effective use of BIM can create more efficient projects in terms of planning, execution, and maintenance. In addition, the study explores planning strategies that support the integration of architecture and MEP, including the selection of environmentally friendly materials, optimal spatial design, and energy efficiency. Comprehensive, sustainable planning can reduce environmental impact, reduce energy consumption, and reduce long-term operating costs. Project control in the context of architectural integration and MEP is also the focus of this study, with emphasis on construction quality monitoring, cost control and risk management. The success of a project often depends on careful control of these aspects. Therefore, this research provides insight into the integration of architecture and MEP in building construction projects and shows how this comprehensive approach can improve efficiency, sustainability, and sustainability as well as overall project outcomes.